THE EFFECT OF LYSINE FORTIFICATION IN SELF-FORMULATED FEED ON THE GROWTH OF BARRAMUNDI (Lates calcarifer) - Atiek Pietoyo; Irvan Firman Syah; Ega Aditya Prama; Indra Kristiana; Dede Suheriawati (Universitas Mataram, 2026)
Fortification of essential amino acids in self-formulated feed is a strategic approach to improve nutrient efficiency and reduce production costs in barramundi (Lates calcarifer) aquaculture. This study aimed to evaluate the effect of dietary lysine supplementation at 0.5% in self-formulated feed on growth performance and feed utilization efficiency. The experiment was conducted from March to June 2023 using a completely randomized design with two treatments: commercial feed as control and self-formulated feed supplemented with lysine, each with three replicates. Fish were reared under controlled conditions and fed to satiation. Observed parameters included weight gain, length increment, specific growth rate (SGR), feed conversion ratio (FCR), feed efficiency (FE), and water quality. The results demonstrated that lysine supplementation significantly improved growth performance and feed utilization. Fish fed lysine-supplemented feed showed higher weight gain (13.87±0.37 g) compared to the control (11.99±0.31 g), as well as lower FCR (1.76±0.10) than commercial feed (2.70±0.10). Feed efficiency was also significantly higher in the lysine treatment (56.8±3.17%) compared to the control (37.1±1.31%). However, no significant difference was observed in SGR between treatments. In conclusion, lysine fortification in self-formulated feed enhances growth performance and feed efficiency of barramundi, indicating its potential as a cost-effective and sustainable feeding strategy in aquaculture practices.